Achieving Broadband Spin‐Correlated Asymmetric Reflection Using a Circular Dichroitic Meta‐Mirror. Issue 3 (22nd January 2021) - Wang, He; Li, Yongfeng; Huang, Lingling; Jing, Yao; Yuan, Qi; Wang, Jiafu; Zhang, Jieqiu; Qu, Shaobo
Abstract: Guiding electromagnetic waves carrying spin angular momentum is an important issue in both optical and microwave communities that thus has intrigued enormous interest in the past few decades. In particular, asymmetrical propagation is seriously considered as a possibility to push the development of encryption communication and electromagnetic circulators, which is a hot area but still a challenge. Circular dichroism, referring to differential absorption of distinct polarization states, provides an alternative scheme to achieve asymmetric propagation in a spin‐correlated way. Here, a paradigm of obtaining broadband asymmetric reflection to push the exploration in this aspect is proposed. With this aim, an N‐shaped resonator loaded with two lumped resistors is designed as a meta‐atom to reveal the amplitude flipping of nearly 0 and 1 for distinct polarization states. Combining with Pancharatnam–Berry phases, the arbitrary phase profile of a designated spin state can be achieved. As a proof‐of‐principle, a robust meta‐mirror is fabricated to acquire broadband electromagnetic focusing under the illumination of left‐handed circularly polarized (LHCP) wave. On the other hand, the reflection of right‐handed circularly polarized (RHCP) wave is substantially suppressed. Both numerical simulation and experimental measurement are carried out to demonstrate the feasibility of this system. Abstract : A paradigm to obtain broadband spin‐correlated asymmetric reflection is proposed. An N‐shaped resonator loaded with two lumped resistors is designed as a meta‐atom to reveal circular dichroism. Assisted by the Pancharatnam–Berry phases, a meta‐mirror is fabricated to acquire broadband electromagnetic focusing under the illumination of left‐handed circularly polarized waves, while the reflection of right‐handed circularly polarized waves is substantially suppressed.